Training to teach science: Experimental evidence from Argentina - Facundo Albornoz; María Victoria Anauati; Melina Furman; Mariana Luzuriaga; María Eugenia de Podestá; Inés Taylor (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2017)
This paper uses a RCT implemented in state schools in Argentina to estimate the learning impact and cost-effectiveness of different teacher training methods: structured curricula and coaching. Our findings suggest that there is a substantial gain in terms of learning for students with teachers being trained using structured curricula and coaching (between 55% and 64% of a standard deviation more than those students in the control group). Coaching teachers does not appear as a cost-effective intervention since the unit cost per 0.1 standard deviation is more than twice the cost of using a structured curriculum only. However, additional coaching is particularly relevant for relatively inexperienced teachers. A structured curriculum and coaching also affect perceptions: teachers enjoyed more teaching Science, they taught more hours of Science and students learned more and developed more skills.
Keywords: C93; I21; I28; 330; Science education; Teacher training; Experimental study